Public art and social media: Street art tourism, sociocultural agency and cultural production in contemporary Lisbon - Castellano, C. G.; Raposo, O. (Community Development Journal, 2024)
This essay engages with Guias do Mocho [Mocho’s Tourist Guides], a bottom-up cultural tourism initiative emerging in Quinta do Mocho, a ‘peripheral’ neighbourhood of Lisbon, as a way of problematizing the relationship between public and street art and social media aesthetics. Scholarship on digital creative industries and street art tourism tends to emphasize the complicities of this kind of cultural experience with neoliberal understandings of the urban space. By examining an example of bottom-up, localized guided tours that operates through social media in the context of peripheral areas of Lisbon, we argue that public art and social media should be seen as part of a more complicated correlation, one in which the affects and effects of creative, site-specific projects are actively developed and expanded in unforeseen ways. Our research demonstrates that public art and social media are mutually developing a renewed economy of attention and system of valorization. The critical examination of both elements is compulsory when measuring the impact of art-driven processes of community development.